Analisis Pembentukan Portofolio Optimal Model Indeks Tunggal Dalam Mengambil Keputusan Investasi Pada Saham Sub Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia - Karnila Ali; Nani Septiana; Nadisa Aristia Putri (Universitas Muhammadiyah Metro, 2026)
Investment is the main key in achieving increased economic growth which is reflected in the ability to increase the growth rate and income level. In this study the author chose a banking company as the object of research. This research was conducted with a quantitative descriptive research method that aimed to find out what stocks were included in the optimal portfolio candidate and also to find out how much the proportion of each stock was, then to find out the return and risk that will be received. The population used in this study were 47 banking stocks listed on the Indonesia Stock Exchange for the period 2020-2023. Based on the analysis that the author had done by calculating using the formula on Ms excel, , there were 11 stocks that were optimal portfolio candidates, namely Bank Raya Indonesia Tbk, Allo Bank Indonesia Tbk, Bank Victoria International Tbk, Bank CIMB Niaga Tbk, Bank Syariah Indonesia Tbk, Bank Panin Dubai Syariah Tbk, Bank Mandiri (Persero) Tbk, Bank Central Asia Tbk, Bank Negara Indonesia Tbk, Bank Maybank Indonesia Tbk, and Bank Pan Indonesia Tbk. Of the 11 companies, the proportion of each selected stock was BNGA with the highest of 0.2655 (26.5%), then BBHI of 0.1412 (14.1%), BRIS of 0.1207 (12.1%), BBCA 0.1102 (11.0%), AGRO by 0.0822 (8.2%), BMRI by 0.0764 (7.6%), PNBN by 0.0583 (5.8%), BVIC by 0.0546 (5.5%), BNII by 0.0466 (4.7%), BBNI by 0.0398 (4.0%), and PNBS by 0.0045 (0.4%). Of the stocks that made up the optimal portfolio had a return of 0.0475 (4.75%) and a risk of 0.0603 (6.03%).